Distribution and sampling of Prostephanus truncatus (Coleoptera: Bostrichidae) and Sitophilus zeamais (Coleoptera: Curculionidae) in maize stores in Benin - Meikle, W.; Markham, R.; Holst, N.; Djomamou, B.; Schneider, H.; Vowotor, K.A. (Oxford University Press, 1998)
The distribution among and within grain stores of 2 grain store pests, Prostephanus Truncatus (Horn) and Sitophilus zeamais Motschulsky were examined over time using different maize cultivars. Incidence in stores was variable between seasons for both species. The b coefficient of Taylor's power law did not differ among maize cultivars. Within-store distribution among cobs could be approximated by the negative binomial and an overall k parameter was estimated for both species. These data were used to develop sampling plans to estimate sample size needed to determine insect density for both pest species over different densities given a desired precision. Sequential sampling stop lines were calculated to determine pest status given action and no-action threshold densities. The possibility of applying the sampling plans as an integrated pest management tool is discussed.